Examining Factors Influencing Governance Effectiveness in Non-Profit Organizations in Saudi Arabia - Alzaidan, Ziyad; Albulayhl, Othman; Alqusumi, Fahad; AlRashidi, Faisal; Almazyad, Faris; ALajlan, Abdulaziz; Alghurayr, Ibrahim; Alsawee, Waleed; Aldahash, Mohammed; Almubark, Khalid (American Journal of Business Science Philosophy, 2025)
This study investigates the determinants of governance effectiveness in non-profit organizations in Saudi Arabia, with a focus on board competency, transparency, stakeholder engagement, compliance, and leadership quality. Adopting a quantitative research design, data were collected from 266 employees working in Saudi non-profits. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. Structural model results revealed that all five predictors had a significant positive effect on governance effectiveness, with stakeholder engagement (β = 0.565) and leadership quality (β = 0.565) emerging as the most influential factors. The model explained 60.4% of the variance in governance effectiveness, indicating substantial explanatory power. The findings highlight that governance effectiveness is multi-dimensional, requiring the integration of stakeholder participation, transparent practices, compliance with regulations, competent boards, and ethical leadership. In the Saudi context, these results align closely with the objectives of Vision 2030, which emphasizes accountability, transparency, and capacity-building in the non-profit sector. It also offers practical recommendations for policymakers and practitioners to strengthen governance through leadership development, stakeholder inclusion, transparency mechanisms, compliance frameworks, and board training.